Characterization of recalcitrant material in leachate from an old landfill by spectroscopic methods - Monteiro, Victória Regina Celso; Barquilha, Carlos Eduardo Rodrigues; Braga, Maria Cristina Borba (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Landfill sanitary leachate is an effluent with complex characteristics that still presents some challenges for treatment. From the stabilization of the organic matter which occurs over the years in a landfill, the leachate biodegradability decreases, decreasing the biological treatment efficiency. The objective of this research was to identify the characteristics of leachate from an old landfill, located in Curitiba-BR, using conventional and spectroscopic methods. Two collects of raw leachate were carried out at the Curitiba Municipal Landfill in different periods, which were denominated P11 and P12. The analyzes performed were pH, COD, BOD, DOC, color and solids, as well as UV-Vis and fluorescence spectroscopies. The results indicated that the leachate was influenced by precipitation taxes and it is possible to infer that this landfill is in the aging process, since the leachate presented recalcitrant characteristics. The organic matter presented a strong humification degree due to the presence of aromatic substances, such as humic and fulvic acids, indicating that physical-chemical treatment should be applied to this leachate. In addition, the spectroscopic analysis brought additional information, with a quicker and lower reagent consumption than conventional methods. Thus, these spectroscopic techniques can be considered promising tools to monitor the leachate, assist in the identification of the landfill decomposition stage, and subsidize the planning for proper leachate treatment.